Limit Pricing Oligopoly Market: Evidence from Tamilnadu Politics - R. Pazhanisamy (ZBW – Leibniz Information Centre for Economics, 2019)
Limit pricing oligopoly market is a hypothetical market explained with various hypotheses in the literature which has limited scope for the real world economic evidence and its application which leads the impact of the operation of such market is mostly unknown among the policymakers and academics. The available literature evidences are mostly neglected to explore the scope of such markets conditions and failed to direct appropriate policies. In India among most of the national level parties and in the states levels there are two only have been surviving over the long periods. This trigger the intuition to inquire into answer the questions a) why the political market is appears to be an oligopolistic market? b) How it maintain the limit pricing policy to deter the entry of new ? c) How the share the market? d) Are they collusive oligopolistic or non collusive? e) Are they price leadership oligopolist or not? f) How could they operate in the long run while some of them closed it even within the short run? Since there are very limited attempts only are available to answers this question. This calls for an enquiry by incorporating the micro economics theory with the political system. This paper is attempted to fill this gap in research.
Keywords: D01; D03; D43; D72; G18; H30; Q12; P48; 330; Limit Pricing Oligopoly; Oligopolitics; Breaking the Oligopoly Politics; Collusive and Non Collusive Politics; Entry Prevention in Politics; Political Micro Economics